Tobacco industry and public health responses to state and local efforts to end tobacco sales from 1969-2020. - Patricia A McDaniel; Ruth E Malone (PLoS ONE, 2020)
BACKGROUND:In June 2019, Beverly Hills, California, became the first American city in the 21st century to pass an ordinance ending the sale of most tobacco products, including cigarettes, and it is unlikely to be the last. Knowledge of previous efforts to ban tobacco sales in the US, both successful and unsuccessful, may help inform tobacco control advocates' approach to future efforts. METHODS:We retrieved and analyzed archival tobacco industry documents. We confirmed and supplemented information from the documents with news media coverage and publicly available state and local government materials, such as meeting minutes and staff reports, related to proposed bans. RESULTS:We found 22 proposals to end the sale of cigarettes or tobacco products from 1969-2020 in the US. Proposals came from five states, twelve cities or towns, and one county. Most came from elected officials or boards of health, and were justified on public health grounds. In opposing tobacco sales bans, the tobacco industry employed no tactics or arguments that it did not also employ in campaigns against other tobacco control measures. Public health groups typically opposed sales ban proposals on the grounds that they were not evidence-based. This changed with Beverly Hills' 2019 proposal, with public health organizations supporting this and other California city proposals because of their likely positive health impacts. This support did not always translate into passage of local ordinances, as some city council members expressed reservations about the impact on small businesses. CONCLUSION:Tobacco control advocates are likely to encounter familiar tobacco industry tactics and arguments against tobacco sales ban proposals, and can rely on past experience and the results of a growing body of retail-related research to counter them. Considering how to overcome concerns about harming retailers will likely be vital if other jurisdictions are to succeed in ending tobacco sales.